The implications of an EMU unemployment insurance scheme for supporting incomes - Holguer Xavier Jara Tamayo; Holly Sutherland (University of Essex, Institute for Social and Economic Research (ISER), 2014)
In this paper we explore the potential of a new unemployment insurance benefit at EMU level to improve the income protection available to the unemployed and their families. The benefit is designed to be additional to existing national provision where this falls short in terms of eligibility (coverage) and the amount payable. The EMU-UI has a common design across countries, which is intended to reduce the extent of current gaps in coverage where these are sizeable due to stringent eligibility conditions, to increase generosity where current unemployment benefits are low relative to earnings and to extend duration where this is shorter than 12 months. Our analysis compares the extent of the effect of these improvements across selected countries from the Monetary Union (Germany, Estonia, Greece, Spain, France, Italy, Latvia, Austria, Portugal and Finland) using EUROMOD to simulate entitlement to the national and EMU-UIs and to calculate the effect on household disposable income. We find that the EMU-UI reduces the risk of poverty for the new unemployed and has a positive effect on income stabilisation. The extent of these effects varies in size across countries for two main reasons: notable differences in design of national unemployment insurance schemes and differences in labour force characteristics across countries, mainly in the proportion of self-employed workers who are typically not covered by national schemes. In countries such as France and Finland there is little effect of EMU-UI on poverty risk and stabilisation, while Greece, Italy and Latvia benefit the most, in particular from the EMU proportional scheme. Our analysis highlights potential areas of future research in terms of improving the design of the EMU-UI and accounting for national or EMU level ways of financing, as well as refinements to the methodology used to assess the effects of transitions to unemployment.
Keywords: C81; H55; I3; 330; Unemployment insurance; European Monetary Union; Household income; Microsimulation